1, 25-dihydroxyvitamin D and cardiometabolic risk in healthy sedentary adults: The FIT-AGEING study. (1st December 2021) - De-la-O, Alejandro; Jurado-Fasoli, Lucas; Lavie, Carl J.; Castillo, Manuel J.; Gutiérrez, Ángel; Amaro-Gahete, Francisco J.
Abstract: Background: A growing body of scientific works investigating the physio-pathological mechanisms behind cardiovascular disease has suggested that vitamin D deficiency could play a key role on its development. However, it remains unclear whether its active form (1, 25-dihydroxyvitamin D [1, 25(OH)2 D] is associated with cardiometabolic risk factors in healthy individuals. The aim of the present study was to investigate the relationships of 1, 25(OH)2 D plasma levels with cardiometabolic risk factors in a sample of healthy sedentary adults. Methods: A total of 73 adults (~53% women; 54 ± 5 years old) were included in the current cross-sectional study. A sex-specific cardiometabolic risk score (MetScore) was calculated for each subject based on clinical parameters ( i.e., waist circumference, systolic and diastolic blood pressure, plasma glucose, high-density lipoprotein cholesterol, and triglycerides) according to the International Diabetes Federation's clinical criteria. Plasma levels of 1, 25(OH)2 D were measured using a DiaSorin Liaison® immunochemiluminometric analyzer. Results: No significant association was detected between 1, 25(OH)2 D and MetScore (β = 0.037, R 2  = 0.001, p  = 0.77), independently of age, sex and fat body mass index. A significant inverse association were observed between 1, 25(OH)2 D and waist circumference (β = −0, 303, R 2  = 0.092, p  = 0.01). These results were consistent after controlling by potential confounders. Conclusion: In summary, the present results suggest that 1, 25(OH)2 D plasma levels are not associated with either cardiometabolic risk factors or insulin resistance in healthy sedentary adults. However, an inverse association of 1, 25(OH)2 D plasma levels with central adiposity was observed in our study sample. Highlights: 1, 25(OH)2 D plasma levels are not associated with neither cardiometabolic risk factors nor insulin resistance in healthy sedentary adults. An inverse association of 1, 25(OH)2 D plasma levels with central adiposity was observed in our study cohort. It is of interest to measure 1, 25(OH)2D when the effects of sunlight exposure or vitamin D supplementation are studied.